A study on Singaporean youths' destination perception of China. - Chew, See Lek. (2012)
China has become a major tourist destination for Singaporeans in recent years. However, there are no studies that looked particularly at Singaporean youths’ perception of China as a destination. Therefore, the purpose of this study is to investigate if there is a difference between Singaporean youths’ pre-visit and post-visit destination perception of China. The study also identified and analyzed six factors affecting their perception of China as a destination. A quantitative research approach was adopted whereby descriptive research was used to examine the relationship between each of the six factors and destination perception. Non-probability sampling design was adopted and data was collected through survey questionnaires. The results of the study confirmed that five factors do influence destination perception of Singaporean youths, with “Infrastructure” being the most influential factor. In addition, a significant difference was found between the pre-visit and post-visit destination perception. The China National Tourist Office can utilize the result of this study to market the country to Singaporean youths more effectively.